Sperm chromatin biological and clinical applications in male infertility and assisted reproduction - Zini, Armand; Agarwal, Ashok (Physician) (Springer, 2011)
Sperm DNA damage is common and has been associated with reduced rates of conception, impaired embryonic development and increased risk of miscarriage. Although the exact causes of sperm DNA damage are unknown, it is clear that infertile men possess substantially higher levels of sperm DNA damage than do fertile men. Written by leading, internationally renowned clinicians and basic scientists with expertise in sperm DNA, Sperm Chromatin: Biological and Clinical Applications in Male Infertility and Assisted Reproduction provides readers with a thoughtful and comprehensive review of the biologica.